Методологічні аспекти організації просторовог орозвитку повоєнної України - Бистряков, Ігор Костянтинович (НУБіП Укрпїни, 2024)
В статті представлена теза доповіді учасника V Міжнар. наук.-практ. конф. «Формування сталого землекористування: проблеми та перспективи» 19 грудня 2024 р. м. Київ

The article reveals methodological aspects of an innovative projective vision of spatial development of Ukraine regarding the implementation of targeted reconstructive actions in the postwar period. The conceptual approach provides for innovative structuring of spatial formations for the effective use of available territorial resources, with an orientation towards overcoming the instability of economic systems
Keywords: просторовий розвиток; модус соціального домінування; стейкхолдери; єдиний економічний простір; spatial development; mode of social domination; stakeholders; single economic area